O impacto do desempenho ESG na reputação corporativa: evidências empíricas do mercado brasileiro - Aguiar, Henrique Correa de (Brasil, 2024)
This study investigates the impact of environmental, social and governance (ESG) performance on the corporate reputation of Brazilian companies. The research analyzed a set of 46 companies operating in the Brazilian market, listed in the Corporate Reputation Monitor (MERCO) in 2023. Through a cross-sectional linear regression analysis, the study sought to identify the relationship between ESG variables and corporate reputation. The results indicate a positive and statistically significant correlation between these variables, suggesting that companies with more robust ESG practices tend to have a more solid and positive reputation. The adoption of ESG practices not only benefits society and the environment, but also contributes to the reputation of companies.